Acquiring Culinary Vocabulary through Realia Media at SMK PGRI 7 Malang - Merlinda, Riza; Hartiningsih, Sri (Attractive : Innovative Education Journal, 2023)
This study explores the process of acquiring culinary vocabulary in English for Specific Purposes (ESP) lessons at SMK PGRI 7 Malang by using realia media. The research focused on tenth-grade culinary arts students and English teachers, with the school as the research object. The qualitative descriptive method proposed three stages for vocabulary acquisition with realia media: the naming, introduction, and recall phases. The findings revealed that the use of realia media assisted in vocabulary acquisition. However, difficulties were encountered in terms of pronunciation and the amount of preparation required. The strengths include convenient accessibility, active student participation, enhancement of skills, and practical utilization of knowledge. However, weaknesses are integrated, and endeavors are made to obtain resources. The use of realia media was advantageous in improving vocabulary skills and increasing student motivation. The study determined that the teacher successfully utilized realia media to introduce culinary language, resulting in learners obtaining crucial skills for the food sector. The challenges were overcome by strategically implementing realia media, which positively affected the tenth-grade students' understanding of language. Implementing this methodical technique cultivated excitement and active participation, enhancing learning a more comprehensive vocabulary. Keywords: English for Specific Purposes, Culinary Vocabulary, Realia Media